2020
DOI: 10.1111/hsc.12941
|View full text |Cite
|
Sign up to set email alerts
|

“It’s kind of hard to go to the doctor’s office if you’re hated there.” A call for gender‐affirming care from transgender and gender diverse adolescents in the United States

Abstract: Research has identified discrimination and a lack of knowledgeable providers as major barriers for transgender and gender diverse (TGD) individuals seeking care, which contributes to greater stress and significant health disparities affecting this population. However, research involving TGD youth is limited. The aim of this study, therefore, was to describe TGD adolescents’ experiences, concerns and needs in healthcare settings, including their feedback on themes previously identified by healthcare providers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 30 publications
(51 reference statements)
2
41
0
Order By: Relevance
“…Given young people's apparent negative outlook with regard to formal support services, and their lack of knowledge regarding how to access appropriate services, it is imperative that services develop greater outreach engagement with LGBTI + youth organisations. They should be able to promote awareness of how their services can support LGBTI + youth's mental health care needs, signpost pathways to accessing services and provide reassurances of affirmative and inclusive practices, and confidentiality—issues that are especially important to LGBTI + youth (Bosse, 2019; Eisenberg et al., 2020; Williams & Chapman, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given young people's apparent negative outlook with regard to formal support services, and their lack of knowledge regarding how to access appropriate services, it is imperative that services develop greater outreach engagement with LGBTI + youth organisations. They should be able to promote awareness of how their services can support LGBTI + youth's mental health care needs, signpost pathways to accessing services and provide reassurances of affirmative and inclusive practices, and confidentiality—issues that are especially important to LGBTI + youth (Bosse, 2019; Eisenberg et al., 2020; Williams & Chapman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…LGBT + young people are at increased risk of mental health and psychosocial issues, including depression, anxiety, self‐harm, suicidal behaviours, post‐traumatic stress disorder, eating disorders and substance use disorders (Bosse, 2019; Marshal et al., 2011; Rodgers, 2017; Sefolosha et al., 2019). Significant disparities also exist between transgender and gender‐diverse (TGD) youth and cisgender youth, with higher rates of depression, self‐harm, suicidality, eating disorders and substance use disorders, and a greater exposure to bullying and harassment among the former (Dowshen et al., 2016; Eisenberg et al., 2020; Price‐Feeney et al., 2020). Despite evidence of increased risk of mental health issues among LGBT + young people, studies indicate less health care utilization and higher unmet treatment needs among LGBT + youth as compared to the non‐LGBT population (Dunbar et al., 2017; Sefolosha et al., 2019; Williams & Chapman, 2011), which some posit may be associated with the difficulties they may experience accessing health care (Rider et al., 2019; Sefolosha et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of such affirming responses have been related to high levels of satisfaction among young people and their families attending paediatric gender clinics (Inwards-Breland et al, 2019;Pullen Sansfaçon et al, 2019;Tollit, Feldman, McKie, & Telfer, 2019). In terms of limitations, research has identified a lack of understanding by healthcare professionals of transgender young people's needs, discrimination, misgendering, and a lack of training about gender diversity (Carlile, 2020;Corliss et al, 2007;Eisenberg, McMorris, Rider, Gower, & Coleman, 2020;Goldenberg et al, 2019;Gridley et al, 2016;Guss et al, 2019;Heard et al, 2018;Strauss et al, 2017;Temple Newhook, Benson, Bridger, Crowther, & Sinnott, 2018). Such lack of understanding on the part of healthcare professionals can lead to transgender young people and their parents foregoing care (Clark, Veale, Greyson, & Saewyc, 2018;Goldenberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Practices that promote empathy, alliance, positive regard and acceptance, and social transitioning among TGD youth (eg, chosen name and pronouns, access to restrooms consistent with gender identity and presentation 30 ) positively impact psychotherapy outcomes for TGD individuals. 15,27,31 Future studies may choose to consider how to best optimize treatment for TGD youth by evaluating the relative effectiveness of different treatment interventions and modalities. Efficacious elements of treatment that could benefit TGD youth could be implemented in schools and community centers through psychoeducation, emotion regulation skills training, and mindfulness for TGD youth who do not readily have access to psychiatric care.…”
Section: Discussionmentioning
confidence: 99%